Enhanced chloroquine sensing on Cr, Fe, Mg, Ni, Si, and Ti-doped zinc oxide nanoclusters: A DFT study - Muz, Iskender; Bulut, Niyazi (Pergamon-Elsevier Science Ltd, 2026)
The detection of chloroquine (CQ), a widely used antimalarial drug with emerging therapeutic roles but potential cardiotoxicity, necessitate the development of sensitive and selective biosensors. This study employs density functional theory (DFT) to systematically screen the adsorption performance and sensing potential of chloroquine on Cr-, Fe-, Mg-, Ni-, Si- and Ti-doped (ZnO)(20) nanoclusters. Among all investigated dopants, the Mg-doped (ZnO)(20) nanocluster exhibits the most favorable characteristics for CQ detection. It shows the highest adsorption energy (-58.11 kcal/mol), the shortest binding distance (2.10 & Aring;) between the drug's N atom and the nanocluster's Zn site, and a significant change in dipole moment after CQ adsorption. Electronic structure analysis reveals that Mg-doping induces the most pronounced reduction in the HOMO-LUMO energy gap after CQ interaction (similar to 13% change), indicating enhanced charge transfer and a strong electrical signal response. The RDG and NCI analyses confirm that the adsorption is primarily governed by weak van der Waals forces (physical adsorption), the distinct electronic perturbation caused by CQ on the Mg-doped surface is notable. The results demonstrate that Mg-doped (ZnO)(20) nanocluster is the most promising candidate for the development of efficient CQ biosensor.
Keywords: ZnO nanoclusters; Chloroquine detection; Adsorption energy; Biosensor; Van der Waals interaction; DFT